The nucleotide sequence of spinach chloroplast methionine elongator tRNA. - Pirtle, R (1981)
The nucleotide sequence of spinach chloroplast methionine elongator tRNA (sp. chl. tRNAm Met) has been determined. This tRNA is considerably more homologous to E. coli tRNAm Met (67% homology) than to the three known eukaryotic tRNAm Met (50-55% homology). Sp. chl. tRNAm Met, like the eight other chloroplast tRNAs sequenced, contains a methylated GG sequence in the dihydrouridine loop and lacks unusual structural features which have been found in several mitochondrial tRNAs.